Direct measurements of the mechanical strength of carbon nanotube - Aluminum interfaces. (December 2017) - Yi, Chenglin; Chen, Xiaoming; Gou, Feilin; Dmuchowski, Christopher M.; Sharma, Anju; Park, Cheol; Ke, Changhong
Abstract: Interfacial load transfer plays a critical role in the bulk mechanical performance of nanofiber-reinforced metallic-matrix nanocomposites (MMNC). In this paper, we investigate the mechanical strength of interfaces in double-walled carbon nanotube (CNT)-reinforced aluminum (Al) nanocomposites by using in situ electron microscopy nanomechanical single-tube pull-out techniques. The nanomechanical measurements reveal the shear lag effect on the CNT-Al interface that is found to possess an average interfacial shear strength (IFSS) of about 28.7 MPa. The study also shows that thermal annealing results in substantially higher binding strength interfaces between CNTs and Al matrices. The average IFSS of CNT-Al interfaces that were thermally annealed at 400 °C is found to reach about 35.3 MPa, a 23% increase from that of the non-annealed interfaces. The maximum load bearing capacity of the annealed interfaces reaches about 304 nN, a 40.1% increase from that of the non-annealed ones (about 217 nN). The findings are useful to better understand the load transfer mechanism in CNT-reinforced MMNC and the tuning and optimization of the reinforcing performance through thermal processing. Graphical abstract: The mechanical strength of interfaces in double-walled carbon nanotube (CNT)-reinforced aluminum (Al) nanocomposites was characterized by using in situ electron microscopy nanomechanical singletube pull-out techniques. The nanomechanical measurements reveal the shear lag effect on the CNT-Al interface and demonstrate that thermal annealing results in substantially higher binding strength interfaces between CNTs and Al matrices.